Muhammadiyah dan NU: Penjaga Moderatisme Islam di Indonesia - Zakiya Darajat (Universitas Negeri Jakarta, 2017)
Islam has been expressed through its adherents in many ways. Sometimes the expression has been judged as hard and even arrogant. This is not the case with Islam in Indonesia which has been shown more friendly expression of Islam. However, the radical movements have challenged this peaceful image of Islam in Indonesian. The research which mainly utilized the library sources has concludes that Islam in Indonesia is still considered to be a moderate Islam and in this case, Muhammadiyah and Nahdlatul Ulama are two organizations which can be seen as the guardians of Islamic moderatism in Indonesia.